Successful hematopoietic cell transplantation in a patient with X‐linked agammaglobulinemia and acute myeloid leukemia. Issue 9 (20th April 2015) - Abu‐Arja, Rolla F.; Chernin, Leah R.; Abusin, Ghada; Auletta, Jeffery; Cabral, Linda; Egler, Rachel; Ochs, Hans D.; Torgerson, Troy R.; Lopez‐Guisa, Jesus; Hostoffer, Robert W.; Tcheurekdjian, Haig; Cooke, Kenneth R.
<x xml:space="preserve">Abstract</x> X‐linked agammaglobulinemia (XLA) is a primary immunodeficiency characterized by marked reduction in all classes of serum immunoglobulins and the near absence of mature CD19+ B‐cells. Although malignancy has been observed in patients with XLA, we present the first reported case of acute myeloid leukemia (AML) in a patient with XLA. We also demonstrate the complete correction of the XLA phenotype following allogeneic hematopoietic cell transplantation for treatment of the patient's leukemia. Pediatr Blood Cancer 2015;62:1674–1676. © 2015 Wiley Periodicals, Inc.